High Estimated Glomerular Filtration Rate Is Associated With Worse Cognitive Performance in the Hypertensive Population: Results From the China H-Type Hypertension Registry Study - Li, Junpei; Yu, Shichao; Tan, Ziheng; Yu, Yun; Luo, Linfei; Zhou, Wei; Zhu, Linjuan; Wang, Tao; Cao, Tianyu; Tu, Jianglong; Bao, Huihui; Huang, Xiao; et al. (Frontiers in Aging Neuroscience, 2022)
Background: Increasing studies have focused on the predictive value of high eGFR on cardiovascular diseases and mortality, however, the association between high eGFR with cognitive function is still not established. Thus, current study aimed to determine the co-relationship between high eGFR and cognitive performance in hypertensive population. Methods: We conducted a baseline cross-sectional study using data from China H-type Hypertension Registry study. Mini-mental State Examination (MMSE) assessment was used to evaluate the cognitive function scale, and serum creatinine was collected to estimate eGFR level. Different MMSE cut-offs were applied in participants with various educational background to define dementia: <24 in participants with secondary school and above education setting; <20 in those with primary school, and <17 in illiterate participants. Results: Total of 9527 hypertensive adults with mean age 63.7 ± 9.8 years and 67% female gender were analyzed. The eGFR cut-off point of 71.52 ml/min per 1.73 m2 was found after adjusting for potential covariates in threshold effect analysis. The MMSE increased significantly with the increment of eGFR (β, 0.27; 95%CI: 0.12 to 0.41) in participants with eGFR<71.52 ml/min per 1.73 m2, and decreased (β, -0.28; 95%CI: -0.39 to -0.17) in participants with eGFR ≥71.52 ml/min per 1.73 m2. Individuals with eGFR ≥ 85 ml/min/1.73m2 have an elevated risk of cognitive impairment than those with eGFR of 65 to 75 ml/min/1.73m2. Subgroup analysis showed that a greater reduction degree of MMSE was observed in female and BMI ≥24 kg/m2 among participants with eGFR ≥ 71.52 ml/min per 1.73 m2. Conclusion: Our findings observed an inverted U-shaped relationship between eGFR and cognitive function. Both low and high eGFR were independently associated with worse cognitive assessment in the hypertensive population.